2003
DOI: 10.1177/0895904803254963
|View full text |Cite
|
Sign up to set email alerts
|

School Choice and Ethnic Segregation

Abstract: Since the 1980s, ethnic segregation has become a feature of the educational landscape in many European countries. The article explores how school choice has influenced this stratification in Dutch primary schools. In contrast to earlier research, the authors found that the ethnic composition of schools plays an important role in the school choice of parents. The study shows that native Dutch parents are significantly more interested in a match between their social and cultural background and the pupil composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 16 publications
(24 reference statements)
3
103
1
7
Order By: Relevance
“…From an ethnic point of view, schools in the large Dutch cities are situated in more varied social environments than schools in small and medium-sized towns in the Netherlands. Generally, Dutch schools in a big-city environment have an ethnically heterogeneous student population but this is not necessarily the case (Karsten, Ledoux, Roeleveld, Felix, & Elshof, 2003). The increasing segregation in education has resulted in the emergence of predominantly 'white' and 'black' schools, particularly in the large cities.…”
Section: Social Competence and The School Contextmentioning
confidence: 99%
“…From an ethnic point of view, schools in the large Dutch cities are situated in more varied social environments than schools in small and medium-sized towns in the Netherlands. Generally, Dutch schools in a big-city environment have an ethnically heterogeneous student population but this is not necessarily the case (Karsten, Ledoux, Roeleveld, Felix, & Elshof, 2003). The increasing segregation in education has resulted in the emergence of predominantly 'white' and 'black' schools, particularly in the large cities.…”
Section: Social Competence and The School Contextmentioning
confidence: 99%
“…La distancia al centro, por consiguiente, se ve muy influenciada por una serie de variables: 1) el estatus social, que influye en la capacidad de los individuos de aumentar el coste de la distancia; 2) la raza o etnia de la unidad familiar; 3) el nivel educativo de los padres (vinculado al estatus socioeconó-mico) (Karsten et al, 2003;Andre-Bechely, 2007;Chen et al, 2011;Sang et al, 2011). En este sentido, hay estudios que muestran que estudiantes cuyas familias tienen un nivel educativo alto realizan viajes de mayor distancia para desplazarse al centro educativo (Bunar y Kallstenius, 2005), mientras que los centros con menor rendimiento académico reclutan a estudiantes que residen en un área de influencia más cercana (Walford, 2003;Butler et al, 2007;Trumberg, 2011).…”
Section: Introductionunclassified
“…Parental choice is also an important factor. There is evidence (for example, Karsten et al, 2003) that this choice can be influenced by differential preferences of different ethnic and social groups. A study by Schneider and Buckley (2001) in Washington, D.C. revealed that parents have a strong behavioural bias toward the demographic characteristics (that is, the country of origin of the parents) of the student population during their choice process, which is in marked contrast to verbal reports of the importance of race.…”
Section: Causes Of Social and Ethnic Segregationmentioning
confidence: 99%